Cal Poly panorama postcard - Philip C. Stelling::::::::: (1973)
Postcard depicting the Cal Poly San Luis Obispo campus. Caption on back reads: 'The Cal Poly campus, as seen in the panoramic view from the famous 'Poly P', is set on the lower slopes of the Santa Lucia Mountains which edge the city. Since its founding in 1901, Cal Poly has grown from a two-year vocational training school to a large and outstanding four-year accredited college. Because of Cal Poly's 'learn by doing' philosophy and truly 'polytechnic' nature, its graduates have earned a reputation for being among the finest technically oriented people in the country.' San Luis Mountain (left) and Bishop' Peak (right) are in the background and the campus is in the foreground.